A Thematic Analysis of the Impact of Community Engagement Studios on Community Experts' Attitudes, Desires, and Understanding of Research - Chioma N. Kas-Osoka; Tiffany Israel; Aima A. Ahonkhai (The University of Alabama, 2023)
Community Engagement Studios (CE Studios) are consultative sessions designed to provide community feedback on all stages of the research process from design to dissemination. CE Studios allow researchers to examine ways to enhance clinical and translational research by engaging with community members. Community members who are part of the patient population or target audience are defined as community experts. The purpose of this study is to examine community experts' attitudes, desires, and understanding of research resulting from their participation in CE Studios. We conducted thematic analysis across three separate questions. Ten major themes emerged from the data: involvement, togetherness, trust, value, confidence, community engagement, community connectedness, encouraging others to participate, increasing knowledge and awareness, and respect. One overarching theme of inclusion was also presented in the data. Results indicate that CE Studios provide a space for community experts to gain a better understanding of the multifaceted research process, provide insight into ways to target historically excluded populations, and increase experts' trust, confidence, and respect for researchers and the research process. Moreover, community experts felt connected to their community by participating in CE Studios and expressed interest in encouraging others to participate. Research studies should capitalize on CE Studios as a strategy to engage community members throughout the research process. Future research should determine whether CE Studios serve as a springboard to other leadership roles for community members and whether patient engagement models have a greater impact on patients and communities of color, rural environments, and other patient populations.